Early Childhood Care and Education (ECCE) in Sub-Saharan Africa: A Critical but Neglected Sector of Education - Sifuna, Daniel N. (Papers in Education and Development, 2018)
Early Childhood Care and Education (ECCE) has been expressed in a diversity of terminologies adopted by international agencies and academics. Furthermore, definitions associated with ECCE are contentious. Most definitions of ECCE are child-focused and stress the holistic nature of the concept, namely recognising the cognitive, emotional and physical needs of children. Research evidence suggests that new entrants into primary schools are better prepared for the school environment and that they make better use of school resources if they have been exposed to pre-school education prior to their entry into the regular school system. Notwithstanding the efforts to promote ECCE in Sub-Saharan African countries, access continues to be a significant challenge. Enrolment rates in pre-schools in the region are often below 10 percent, mainly on account of the limited facilities available, as well as because of poverty.